(untitled) (Journal of Partial Differential Equations, 2020)
In this paper, we investigate a reaction-diffusion equation u_t-du_xx=au+_0^tu^p(x,τ)dτ+k(x) with double free boundaries. We study blowup phenomena in finite time and asymptotic behavior of time-global solutions. Our results show if _-h_0^h_0k(x)ψ_1 dx is large enough, then the blowup occurs. Meanwhile we also prove when T^*